A Sacrificial PLA Block Mediated Route to Injectable and Degradable PNIPAAm-Based Hydrogels - Tebong Mbah, Vernon (Polymers (Basel), 2020)
Thermoresponsive poly(N-isopropylacrylamide) (PNIPAAm)-based injectable hydrogels represent highly attractive materials in tissue engineering and drug/vaccine delivery but face the problem of long-term bioaccumulation due to non-degradability. In this context, we developed an amphiphilic poly(D,L-lactide)-b-poly(NIPAAm-co-polyethylene glycol methacrylate) (PLA-b-P(NIPAAm-co-PEGMA)) copolymer architecture, through a combination of ring-opening and nitroxide-mediated polymerizations, undergoing gelation in aqueous solution near 30 °C. Complete hydrogel mass loss was observed under physiological conditions after few days upon PLA hydrolysis. This was due to the inability of the resulting P(NIPAAm-co-PEGMA) segment, that contains sufficiently high PEG content, to gel. The copolymer was shown to be non-toxic on dendritic cells. These results thus provide a new way to engineer safe PNIPAAm-based injectable hydrogels with PNIPAAm-reduced content and a degradable feature.